Cerebral dopamine neurotrophic factor alleviates Aβ25-35-induced endoplasmic reticulum stress and early synaptotoxicity in rat hippocampal cells. (28th October 2016) - Zhou, Wei; Chang, Lirong; Fang, Yuan; Du, Zunshu; Li, Yan; Song, Yizhi; Hao, Fei; Lv, Liying; Wu, Yan
Highlights: ER stress could be triggered by Aβ treatment at early stage in primary neurons. CDNF alleviates Aβ-induced early synaptotoxicity. CDNF protects against Aβ-induced ER stress. Abstract: Alzheimer's disease (AD) is an age-related progressive neurodegenerative disease, and early stage AD is characterized by synaptic dysfunction generally ascribed to soluble oligomers of amyloid-beta (Aβ). Neurotrophic factors are promising for AD treatment and are integrally involved in neuronal growth, survival and maintenance. Cerebral dopamine neurotrophic factor (CDNF) was recently discovered to have beneficial effects on long-term memory. The present study explored the synaptoprotective effects of CDNF in Aβ-treated primary hippocampal cells. Immunofluorescent analysis of synaptophysin and postsynaptic density protein 95 (PSD95) puncta densities in the group of pretreatment with CDNF before Aβ exposure revealed significant improvements compared to Aβ group. In addition, pretreatment with CDNF reduced the expression levels of endoplasmic reticulum (ER) stress-related proteins, including Bip (also known as GRP78), phosphorylation of eukaryotic translation initiation factor 2 subunit α (peIF2α), phosphorylation of c-Jun N-terminal kinase (pJNK), and cleaved caspase 3, which are increased by Aβ treatment at early stage. Our results revealed protective effects of CDNF on Aβ-induced synaptotoxicity and ER stress, implying that CDNF may protect against Aβ-induced synaptotoxicity through suppression of ER stress. CDNF could be a potential drug candidate for early AD treatment.